Episodic Ataxia Mutations in Kv1.1 Alter Potassium Channel Function by Dominant Negative Effects or Haploinsufficiency - Zerr, Patricia (J Neurosci, 1998)
Subunits of the voltage-gated potassium channel Kv1.1 containing mutations responsible for episodic ataxia (EA), a human inherited neurological disease, were expressed in Xenopus oocytes. Five EA subunits formed functional homomeric channels with lower current amplitudes and altered gating properties compared with wild type. Two EA mutations located in the first cytoplasmic loop, R239S and F249I, yielded minimal or no detectable current, and Western blot analysis showed reduced protein levels. Coinjection of equal amounts of EA and wild-type mRNAs, mimicking the heterozygous condition, resulted in current amplitudes and gating properties that were intermediate between wild-type and EA homomeric channels, suggesting that heteromeric channels are formed with a mixed stoichiometry of EA and wild-type subunits. To examine the relative contribution of EA subunits in forming heteromeric EA and wild-type channels, each EA subunit was made insensitive to TEA, TEA-tagged, and coexpressed with wild-type subunits. TEA-tagged R239S and F249I induced the smallest shift in TEA sensitivity compared with homomeric wild-type channels, whereas the other TEA-tagged EA subunits yielded TEA sensitivities similar to coexpression of wild-type and TEA-tagged wild-type subunits. Taken together, these results show that the different mutations in Kv1.1 affect channel function and indicate that both dominant negative effects and haplotype insufficiency may result in the symptoms of EA.